Childhood optic neuritis clinical features and outcome. Issue 9 (16th June 2010) - Absoud, Michael; Cummins, Carole; Desai, Nivedita; Gika, Artemis; McSweeney, Niamh; Munot, Pinki; Hemingway, Cheryl; Lim, Ming; Nischal, Ken K; Wassmer, Evangeline
Abstract : Aim: To describe clinical features and outcome of a series of children with first-episode optic neuritis investigated in three paediatric neurology centres. Methods: Databases were searched to identify children (<16 years) with optic neuritis and life table analysis was used. Results: 44 children (female/male ratio 1.8) median age 10.9 years were followed up for median 1 year. Optic neuritis was unilateral in 43%. Maximal visual deficit was severe (<6/60) in 77%, with full recovery in 70%. Cumulative probability of developing MS (11/44) or NMO (3/44) at 2 years was 0.45. Relapsing optic neuritis was a strong predictor for development of MS or NMO. A positive MRI (>1 brain T2 hyperintense lesion) was a strong predictor for development of MS. Discussion: Childhood optic neuritis is associated with severe visual deficit with good recovery. An initial abnormal MRI brain scan or relapsing optic neuritis should alert the clinician to MS or NMO diagnosis.